SALA DE RECURSOS MULTIFUNCIONAL E REPRESENTAÇÃO DA ESCRITA: ANÁLISE DA RESOLUÇÃO 13/2007, NORMATIVA 16/2011 E FICHA DE REFERÊNCIA PEDAGÓGICA - Nogueira, Amarili Sequeira (2015)
This dissertation have like a main goal to analyze the publics inclusion policies, especially rules 13/2007 (BRAZIL, 2007), the Guidance Manual: Implementation Program of Multifunctional Resource Rooms (BRAZIL, 2010) Instruction No. 16/2011 SUED / SEED (Paraná, 2011), to discuss the criteria which they propose for the forwarding of students for Multifunctional Resource Room Type I and the relation that these criteria have with representations about student`s writing. The theoretical referential that based this research to realize the analysis of publics inclusion policies is Social Representation (Moscovici, 2003; OSTI 2004, 2010). As methodology, documentary research was used (Lüdke, André, 1986) from the perspective of qualitative research. First was selected the documents to be analyzed and then passed to the analysis of these with the help of bibliographic research. The collected data lead us to infer that the competence writing is criteria for forwarding of students at the Specialized Educational Service in SRM Type I, because according to the items to be examined by the Portuguese teachers at the Pedagogical Reference Record, question if students make orthographic changes or inadequately employ accentuation, punctuation and agreement according to formal norms. It was possible to infer from the presented data in that record that it may not be clear enough for teachers realize properly a description of the listed items, which is quite complicated, considering that an evaluation with no real understanding of what and how to evaluate can generate an improper forwarding to specialized educational services in SRM Type I due to the representation of writing these documents.